(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In 2014 democratic electoral system, citizens voted against government officials believed to be corrupt thus providing politicians with a powerful incentive to match their public pronouncements with concrete demonstrations of personnel and political integrity. However, we must remember that democratic changes are a long term commitment. The fight against corruption cannot be a One-Man show or relegated uniquely to political leadership. Anti-corruption strategies are most effective if they are inclusive, systematic, and structured integrating all institutions and policies - investigation prosecution and prevention. Political corruption is perhaps the fountainhead of most corruption in the system. The high cost of managing elections, mostly funded by black money continues to sustain an underlying rationale supporting corruption among political parties. Corruption is a potential dominating issue but the political voice is not a single issue matter. A vibrant society can play a significant role in the fight against corruption, legitimizing political leadership, and counterbalancing contrast structures to ensure transparency and accountability.